A Descriptive Analysis of Team-Teaching Method Application for Young Learners in Integrated Islamic Elementary School - Hafni, Astrida; Ningrum, Diah Widya (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2024)
This descriptive analysis explores the application of the team-teaching method for young learners, focusing on a case study at an elementary school in North Sumatra, Indonesia. The study investigates the planning, implementation, evaluation, and obstacles of team teaching in fourth-grade classrooms. Qualitative data was gathered through observations, interviews, and documentation. Findings reveal collaborative lesson planning between core and assistant teachers, with a clear division of roles. Implementation involves whole team participation, with one teacher delivering material while the other assists and supervises students. Evaluation encompasses teacher feedback and student assessment, utilizing summative and formative methods. Obstacles include uneven attention distribution and student dependency on assistant teachers, with proposed solutions such as class restructuring and fostering student independence. Recommendations include continuous teacher development, principal oversight, and student engagement in the learning process. Overall, the study underscores the importance of collaborative teaching methods for enhancing student learning outcomes and addressing challenges in the educational environment.